Campus Compact Luncheon with guest speaker Senator Ted Kennedy in the Coolidge Room in Ballou Hall. Photo 200 - Ko, Melody (Tufts Archival Research Center, 2008)
Campus Compact Luncheon with guest speaker Senator Ted Kennedy in the Coolidge Room in Ballou Hall.